2014
DOI: 10.2147/opth.s59452
|View full text |Cite
|
Sign up to set email alerts
|

Homonymous hemianopia: challenges and solutions

Abstract: Stroke is the most common cause of homonymous hemianopia (HH) in adults, followed by trauma and tumors. Associated signs and symptoms, as well as visual field characteristics such as location and congruity, can help determine the location of the causative brain lesion. HH can have a significant effect on quality of life, including problems with driving, reading, or navigation. This can result in decreased independence, inability to enjoy leisure activities, and injuries. Understanding these restrictions, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 69 publications
(84 reference statements)
3
76
0
1
Order By: Relevance
“…One in four patients in this study reported a vision problem. Problems with vision after infarction are often underreported, because either patients do not recognize their own problem [29] or the physician fails to recognize the problem as vision related [30][31][32]. Our findings also probably underestimate the real prevalence of vision problems because our data are self-reported.…”
Section: Discussionmentioning
confidence: 68%
“…One in four patients in this study reported a vision problem. Problems with vision after infarction are often underreported, because either patients do not recognize their own problem [29] or the physician fails to recognize the problem as vision related [30][31][32]. Our findings also probably underestimate the real prevalence of vision problems because our data are self-reported.…”
Section: Discussionmentioning
confidence: 68%
“…In our opinion, early identification of visual problems in acute stroke patients would benefit patients, caregivers, and the healthcare system in general. Optimal multidisciplinary structures for this should be established, as also suggested by otherss . Stroke‐related visual field defects are a silent, but serious handicap, easily overlooked by healthcare workers, patients, and surroundings.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, damage to the occipital, parietal, or temporal lobes caused by cerebral insults, including stroke, trauma, tumor, or brain surgery, results in severe visual field defects. Lesions affecting postchiasmal afferent nerve pathways generally produce homonymous visual field loss, which can be a hemianopia (one-half of an eye's visual field) or quadrantanopia (one-fourth of an eye's visual field) depending on the location of the lesion, with high impact upon the patient's quality of life [6,7].…”
Section: Introductionmentioning
confidence: 99%